Determination of thermal characterisation by photopyroelectric technique: application on textile. Issue 1 (2nd January 2017) - Mami, Amel; Najoua, Bennaji; Mellouki, Imen; Yacoubi, Noureddine
Abstract: In this paper, a thermal performance of textile samples by photopyroelectric technique from only logarithm of amplitude pyroelectric signal is presented. A special case of normalised pyroelectric signal relative to an empty pyroelectric sensor is implemented in order to avoid experimental factor and simplify final expression of pyroelectric voltage. In addition, we have simulated a fault detector based on a microcontroller PIC16F877A in order to provide low cost protection of the lock-in amplifier. Obtained thermal parameters of single jersey knitted fabrics made of 100% cotton, 50% cotton–50% acrylic fibre and 100% acrylic fibre are measured by fitting theoretical curves to experimental ones of photopyroelectric amplitude signal according to modulation frequency root. These measurements were in good agreement with corresponding values extracted from photopyroelectric phase signal and the reported literature values.